2020
DOI: 10.1038/s41598-020-62527-5
|View full text |Cite
|
Sign up to set email alerts
|

3′-Sialyllactose prebiotics prevents skin inflammation via regulatory T cell differentiation in atopic dermatitis mouse models

Abstract: 3′-Sialyllactose (3′-SL), a natural prebiotic, maintains immune homeostasis and exerts antiinflammatory and anti-arthritic effects. Although regulatory T cells (Tregs) prevent excessive inflammation and maintain immune tolerance, the effect of 3′-SL on Treg regulation is unclear. This study aimed to investigate the effect of 3′-SL on Treg responses in atopic dermatitis (AD) pathogenesis. Oral administration of 3′-SL reduced AD-like symptoms such as ear, epidermal, and dermal thickness in repeated topical appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…During the last decade, several studies pointed out the beneficial and anti-inflammatory effects of a high-fiber diet and prebiotics such as poly- and oligosaccharides in murine models of atopic dermatitis [ 164 , 165 , 166 , 167 ]. Besides dietary fibers, the impact of probiotic supplementations on experimental atopic dermatitis was intensively studied, revealing a changed gut microbiota and the associated increase in SCFAs as a possible therapeutic mechanism [ 168 , 169 , 170 , 171 ].…”
Section: Short Chain Fatty Acidsmentioning
confidence: 99%
“…During the last decade, several studies pointed out the beneficial and anti-inflammatory effects of a high-fiber diet and prebiotics such as poly- and oligosaccharides in murine models of atopic dermatitis [ 164 , 165 , 166 , 167 ]. Besides dietary fibers, the impact of probiotic supplementations on experimental atopic dermatitis was intensively studied, revealing a changed gut microbiota and the associated increase in SCFAs as a possible therapeutic mechanism [ 168 , 169 , 170 , 171 ].…”
Section: Short Chain Fatty Acidsmentioning
confidence: 99%
“…Importantly, we show that the anti-inflammatory effects of 3’SL in vitro translated in attenuated atherosclerosis lesion development in vivo . Anti-inflammatory effects of 3’SL in vivo were previously shown in mouse models of rheumatoid arthritis and atopic dermatitis 40, 81 . However, the authors administered 3’SL orally and thus it cannot be excluded that the anti-inflammatory phenotypes are due to likely drastic changes in the gut microbiome 34, 81 .…”
Section: Discussionmentioning
confidence: 80%
“…Administration of 3′-sialyllactose reduced ear, epidermal, and dermal thickness in a mouse model of atopic dermatitis, downregulated the expression of pro-inflammatory and atopic dermatitis-related cytokines, and suppressed mast cell infiltration and IgE levels. Further, 3′-sialyllactose induced transforming growth factor-β-mediated Treg differentiation in an in vitro system [ 103 ]. Experiments in both in vitro and ex vivo systems showed that 3′-sialyllactose restored IL-1β-induced reduction of COL2A1 expression as well as promoted the accumulation of sulfated proteoglycan, which is a critical factor for cartilage regeneration in OA development [ 104 ].…”
Section: Candidate Therapeutic Agentsmentioning
confidence: 99%